2012
DOI: 10.4172/2157-7560.1000134
|View full text |Cite
|
Sign up to set email alerts
|

Bell’s Palsy Cases Following Administration of Influenza A (H1N1) 2009 Monovalent Vaccine Reported to the Vaccine Adverse Event Reporting System (VAERS)

Abstract: Methods:We retrospectively reviewed reports to VAERS and available medical records of persons

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Cano et al. reported that during influenza vaccination‐related Bell's palsy, H1N1 influenza A vaccination emerged as a cause in two (3.1%) cases of bilateral facial palsy from a total of 65 patients, whereas seasonal vaccination emerged as a cause in one (3.6%) case of bilateral facial palsy from a total of 32 patients . In that study, the rate of influenza vaccine‐related bilateral facial palsy seems more frequent.…”
mentioning
confidence: 74%
“…Cano et al. reported that during influenza vaccination‐related Bell's palsy, H1N1 influenza A vaccination emerged as a cause in two (3.1%) cases of bilateral facial palsy from a total of 65 patients, whereas seasonal vaccination emerged as a cause in one (3.6%) case of bilateral facial palsy from a total of 32 patients . In that study, the rate of influenza vaccine‐related bilateral facial palsy seems more frequent.…”
mentioning
confidence: 74%
“… 44 Moreover, a study conducted in Australia also observed intussusception in children aged 1 to 21 days after immunization with RotaTek(®, a popular brand of rotavirus vaccine) and this was consistent with the finding in a study in Mexico after immunization with another brand, Rotarix(® 45 . These findings are related to concerns which led to the withdrawal of the rotavirus vaccine, Rotashield(® from the USA market demonstrating the need to study the safety of the rotavirus vaccine extensively 46 . The serious AEFIs in the yellow fever multi-centre study, yellow fever vaccine associated neurological disease (YFVAND) and suspected yellow fever vaccine associated viscerotropic disease (YFVAVD) have been observed in other studies and must be noted carefully by vaccine program managers and Expanded Program on Immunization managers 47 , 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Most AEFIs resulting from bad manufacturing practices have largely occurred during the introduction of new vaccines for outbreaks which need quick interventions to avoid the rapid spread of disease. Examples of such AEFIs include Bell's palsy resulting from the inactivated nasal flu vaccine and intussusception from the rotavirus vaccine, Rotashield 16 , 17 . To avoid these AEFIs or reduce their prevalence to the barest minimum, vaccines need to be rigorously monitored for AEFIs especially when they are newly introduced, despite their potential for infection prevention.…”
Section: Introductionmentioning
confidence: 99%